2013
DOI: 10.3389/fnins.2013.00201
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic control of cognitive flexibility in humans and animals

Abstract: Striatal dopamine (DA) is thought to code for learned associations between cues and reinforcers and to mediate approach behavior toward a reward. Less is known about the contribution of DA to cognitive flexibility—the ability to adapt behavior in response to changes in the environment. Altered reward processing and impairments in cognitive flexibility are observed in psychiatric disorders such as obsessive compulsive disorder (OCD). Patients with this disorder show a disruption of functioning in the frontostri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
182
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(188 citation statements)
references
References 293 publications
3
182
0
Order By: Relevance
“…Flexibility refers to the ability to revise a course of action in the face of unpredicted difficulties or obstacles, change one's own ideas in the light of new evidence, and adapt to changes that different life epochs or contingent situations may require. Lack of flexibility may result in great distress for a person undergoing sudden and/or important life changes, and is an important aspect of several psychiatric disorders, such as obsessive personality or delusional disorder (26).…”
Section: Toward a New Definition Of Mental Healthmentioning
confidence: 99%
“…Flexibility refers to the ability to revise a course of action in the face of unpredicted difficulties or obstacles, change one's own ideas in the light of new evidence, and adapt to changes that different life epochs or contingent situations may require. Lack of flexibility may result in great distress for a person undergoing sudden and/or important life changes, and is an important aspect of several psychiatric disorders, such as obsessive personality or delusional disorder (26).…”
Section: Toward a New Definition Of Mental Healthmentioning
confidence: 99%
“…Visual discrimination learning requires perceptual learning and memory processing [1,2], while reversal learning assesses behavioral flexibility of learning [3,4]. Abnormalities in visual discrimination learning have been shown in patients with depression, autism, and Alzheimer's disease, while impairments of reversal learning have been shown in patients with schizophrenia and Alzheimer's disease [5,6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Although it was predicted from the inverted U-shaped relationship between DA and cognitive performance that individuals responding positively to amphetamine should have low DA levels at baseline, this is likely to depend on many factors including brain region of interest, DA D1/D2 receptor activation and task features (Floresco, 2013;Klanker et al, 2013). For example, it has been suggested that DA may have opposing roles in the striatum and prefrontal cortex in terms of modulating behavioural flexibility and stability (Cools and D'Esposito, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Human studies demonstrate the importance of considering individual differences in response to pharmacological treatment (Klanker et al, 2013). For example, improvement after amphetamine has been shown to be dependent on baseline performance, such that low performers had the greatest improvement (Mattay et al, 2000;Allman et al, 2010) and this has also been shown for methylphenidate (Finke et al, 2010;del Campo et al, 2013).…”
Section: Significance Statementmentioning
confidence: 99%
See 1 more Smart Citation